Spectroscopic Studies on Ternary Complexes of Copper(II) with Some Amino Acids - Kumar Kashyap, Anil; Kashyap, Anupama; Mohabey, Hemlata (Asian Journal of Chemistry, 2010)
[Cu(AB)] complex has been prepared where A is primary ligand i.e. valine and B is secondary ligand i.e. serine. The electronic and ESR spectra of the complex suggest the geometry of the complex to be distorted octahedral it prossess D4th symmetry.